Theta‐alpha Oscillations Characterize Emotional Subregion in the Human Ventral Subthalamic Nucleus. Issue 2 (23rd November 2019) - Rappel, Pnina; Grosberg, Shai; Arkadir, David; Linetsky, Eduard; Abu Snineh, Muneer; Bick, Atira S.; Tamir, Idit; Valsky, Dan; Marmor, Odeya; Abo Foul, Yasmin; Peled, Or; Gilad, Moran; et al.
Abstract: Background: Therapeutic outcomes of STN‐DBS for movement and psychiatric disorders depend on electrode location within the STN. Electrophysiological and functional mapping of the STN has progressed considerably in the past years, identifying beta‐band oscillatory activity in the dorsal STN as a motor biomarker. It also has been suggested that STN theta‐alpha oscillations, involved in impulse control and action inhibition, have a ventral source. However, STN local field potential mapping of motor, associative, and limbic areas is often limited by poor spatial resolution. Objectives: Providing a high‐resolution electrophysiological map of the motor, associative and limbic anatomical sub‐areas of the subthalamic nucleus. Methods: We have analyzed high‐spatial‐resolution STN microelectrode electrophysiology recordings of PD patients (n = 303) that underwent DBS surgery. The patients' STN intraoperative recordings of spiking activity (933 electrode trajectories) were combined with their imaging data (n = 83 patients, 151 trajectories). Results: We found a high theta‐alpha (7–10 Hz) oscillatory area, located near the STN ventromedial border in 29% of the PD patients. Theta‐alpha activity in this area has higher power and lower central frequency in comparison to theta‐alpha activity in more dorsal subthalamic areas. When projected on the DISTAL functional atlas, the theta‐alpha oscillatory area overlaps with the STN limbic subarea. Conclusions: We suggest that theta‐alpha oscillations can serve as an electrophysiological marker for the ventral subthalamic nucleus limbic subarea. Therefore, theta‐alpha oscillations can guide optimal electrode placement in neuropsychiatric STN‐DBS procedures and provide a reliable biomarker input for future closed‐loop DBS device. © 2019 International Parkinson and Movement Disorder Society